A relação morfologia-ortografia: um estudo sobre as representações de alunos do ensino fundamental - Duarte, Taiçara Farias Canez (2010)
This research, which is connected to studies of the comprehension of the writing acquisition processes, aims at mapping students representations regarding the orthography and the morphology of Brazilian Portuguese, as well as analyzing the effects of orthography teaching tasks that address the morphology aspects of the orthographic performance and of the representational changes that may happen. The research was carried out in two steps with elementary school students in a public school in Pelotas, RS. By using three tools for data collection and an interview, the fist step evaluated the knowledge students have about certain morphemes of the language and analyzed whether there is a relation between their knowledge about the morphemes and their orthographic performance. The second step consisted of developing a practice to teach orthographic rules with a morphological-grammatical basis and observing the effect of this practice on the student s orthographic performance; modifications may be interpreted as representational changes regarding this knowledge under investigation. In general, results show that students manipulate the morphemes in the language, although the control they have over these processes is related to the type of morpheme, since some are more accessible than others. During the first step of the study, in which the suffix that forms occupations, the negative prefix in-, and verbal flexion were worked on, the students, in general, used the selected suffixes to form agentives and verbally explained their knowledge about the prefix easily. However, they could not verbalize their knowledge about the verbal flexion, even though they had used the verb endings according to verbal paradigms. Regarding the effect of the didactic interventions, there is evidence that work on the explicitation of the relation between morphemes and orthography can make the student re-elaborate his/her representations; however, this result will also be influenced by the type of morpheme under study. On one hand, data collected during the second step show that students have improved regarding the comprehension and the spelling of the morpheme esa. On the other hand, the same evolution was not observed in relation to the knowledge about verbal flexion. In general, the results of the research show the need to carry out studies to investigate the relation between the morphemes of the language and the learning of these units so that verbal explicitation can be achieved.